The Good, the Bad and the Ugly! A Paradigmatic Analysis of Adultery Trope Variances in Movies - Karippara, Malavika Sunil; Barclay, Francis Philip; Sasidharan, Akhila (Unisia, 2023)
To investigate sexist variances in the narratives of Malayalam movies concerning the portrayal of adultery, a semiotic analysis employing paradigmatic tradition is used. Analyzing the portrayal patterns, this study identifies and characterizes three typical adultery narrative devices (or tropes) that sexist: the “Good” Adultery (between a married man and an unmarried woman who is in a long-term relationship with the adultering partner), the “Bad” Adultery (between a married man and a woman with unclear marital status [such as a sex worker] or an unmarried woman who engages in a short-term relationship with the adultering partner); and the “Ugly” adultery (between a [married or unmarried] man and a married woman in a short-term relationship). Gender discrimination is identified in these variations, regarding the roles the man and woman assume in adulterous relationships, characterization of them and their affairs, fabrication of narratives, and the responses of the spouses (from acceptance and accommodation to rejection and revenge).